1996
DOI: 10.1073/pnas.93.26.15030
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and structural analysis of mutant CD4 receptors that are defective in HIV gp120 binding

Abstract: The T-cell antigen coreceptor CD4 also serves as the receptor for the envelope glycoprotein gp120 of HIV. Extensive mutational analysis of CD4 has implicated residues from a portion of the extracellular amino-terminal domain (D1) in gp120 binding. However, none of these proteins has been fully characterized biophysically, and thus the precise effects on molecular structure and binding interactions are unknown. In the present study, we produced soluble versions of three mutant CD4 molecules (F43V, G47S, and A55… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
47
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 41 publications
6
47
0
Order By: Relevance
“…Analysis of the resulting binding curves ( Fig. 2A) returned an affinity of 8 nM, in very good agreement with previously reported data using the same technique (38,39). To check whether our protein undergoes conformational changes upon CD4 binding, we monitored the binding of gp120 to mAb 17b, both in the presence and in the absence of sCD4.…”
Section: Time-course Expression and Purification Of Recombinant Gp120supporting
confidence: 88%
“…Analysis of the resulting binding curves ( Fig. 2A) returned an affinity of 8 nM, in very good agreement with previously reported data using the same technique (38,39). To check whether our protein undergoes conformational changes upon CD4 binding, we monitored the binding of gp120 to mAb 17b, both in the presence and in the absence of sCD4.…”
Section: Time-course Expression and Purification Of Recombinant Gp120supporting
confidence: 88%
“…Deviations of the CD4 structure in the complex from the free state were measured as described 39 . Deviations were taken as significant when the root-mean-square (r.m.s.)…”
Section: Structure Analysismentioning
confidence: 99%
“…If so, to what state and, in reverse, how does CD4 binding lead to the state seen in this ternary complex? CD4-gp120 binding kinetics are complex 39 , and microcalorimetry reveals unusually large ΔH and compensating TΔS values for soluble CD4 binding to gp120 (M. L. Doyle, personal communication). These exceptional CD4-binding thermodynamics are suggestive of a large conformational change and are similar for both full-length and core gp120, supporting the relevance of our structural observations on core gp120.…”
Section: Conformational Change In Core Gp120mentioning
confidence: 99%
“…Furthermore, sCD4 has been reported to bind to envelope proteins, including IIIB gp120, with K D values of 22 to 35 nM (12,59,88). Another study reported K D values in the range of 2.2 to 16 nM for a range of anti-CD4bs Fab fragments (including Fab b12) to MN gp120 (62).…”
Section: Fig 2 Vhh and Mab B12 Icmentioning
confidence: 99%